A simplified approach to numerical simulation of LFW process of Ti6Al4V alloy: investigation on friction and temperature. Issue 9 (October 2016) - Maio, L.; Franco, F.; Squillace, A.; Lecce, L.
Abstract In the present study, the process modeling of linear friction welding of titanium alloy Ti6Al4V is carried out. Two major stages of the process as warm-up and osci-forging are identified and simulated consecutively to generate the temperature field within the model. A transient, two-dimensional, nonlinear thermal model with moving heat source is developed for the purpose using finite element approach. An implicit solution scheme is employed in numerical analysis to solve instationary thermomechanical problem. Good agreement between the numerical results and the experimental measurements available in the literature is found. The presented results can guide the design of welded joints through LFW processes.